Strengthening Indonesia’s Waste Management Laws: Compliance with Public Health and Marine Conservation Norms - Maskun, Maskun; Mohamad Khalid, Rasyikah; Ratnawati, Ratnawati; Mutawalli Mukhlis, Muhammad; Anggara, Wira; Ramli, Rafika Nurul Ramadani (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2024)
Study examines the legal accountability of household waste management in Makassar City within the framework of Indonesian environmental law and its alignment with Sustainable Development Goals, such as SDG 3 “Good Health and Well-Being” and SDG 14 “Life Below Water”. Employing a normative and empirical legal research approach, the study integrates primary data from legal instruments and field observations with secondary legal sources. The findings highlight that ineffective enforcement of criminal sanctions has contributed to the persistence of poor waste management practices. Instead, administrative sanctions, such as fines and corrective measures, have demonstrated greater effectiveness in ensuring compliance. Additionally, a lack of public awareness and inadequate waste segregation infrastructure further exacerbate waste management challenges. Data analysis from the National Waste Management Information System or Sistem Informasi Pengelolaan Sampah Nasional for 2020 until 2023 reveals that nearly 41% of total waste in Indonesia remains unmanaged, while Makassar alone generates approximately 1,000 tons of waste per day. Given these challenges, this study advocates for the enhancement of legal enforcement mechanisms by prioritizing administrative over criminal sanctions, strengthening public participation, and integrating sustainable waste management policies. Comparative insights from countries with successful waste management strategies, such as Japan and Sweden, underscore the importance of policy coherence, stakeholder collaboration, and technological innovations. The study concludes that an effective regulatory framework, coupled with community engagement and structured law enforcement, is essential for achieving intergenerational sustainability and environmental protection in Indonesia.